Drooling in Cerebral Palsy - Audrey Shavell (South African Journal of Communication Disorders, 1977)
A review of methods of treatment used over the past twelve years in the alleviation of Drooling in Cerebral Palsy is considered. A small group of  patients remain persistent droolers in spite of intensive conservative treatment . Information  was obtained on patients who had been referred for oral surgery between October 1973 - December 1976 to determine whether any common factors would be found  among them which might assist in the selection of future cases for oral surgery; predict the outcome of  future  surgery more accurately; assess the improvement achieved in the twenty cases of  this series; and indicate post-operative complications.Data was obtained from  an analysis of  the results of  a questionnaire completed by speech therapists on patients who had all undergone bilateral submaxillary gland excision com-bined with parotid duct elongation and posterior relocation. The oral surgery was carried out by the late Dr. Isidore Kaplan formerly  honorary plastic surgeon, Forest Town Cerebral Palsy School.